Coffee - cardamom, black pepper and mandarin mixed cropping system - a case study - RAJENDRA HEGDE, M M HOSMANI, V S KORIKANTHIMATH, RAVINDRA MULGE, (Journal of Spices and Aromatic Crops, 1997)
Experiments were conducted at Chettalli, a predominantly coffee growing area in Kodagu District (Karnataka, India) to study the yield potential of coffee (Coftea robusta), cardamom (Elettaria cardamomum), black pepper (Piper nigrum) and mandarin (Citrus reticulata) in a mixed cropping system. Dry yield of coffee was significantly higher when it was grown as mono crop (2163 kg/ha) compared to mixed crop (1568 kg/ha). Cardamom when introduced as a single hedge by trimming the side branches of alternate rows of coffee, recorded an yield of 204.83 kg/ha. Black pepper vines trained on live standards of shade trees yielded 1222.15 kg/ha. Mandarin was severely infested with greening disease and there was no appreciable yield. The study indicated the feasibility of inroduction of high value crops like cardamom and black pepper as mixed crops for increasing the production and productivity of coffee plantations.